Penentuan Kadar Hidrokuinon dan Asam Retinoat Pada Krim Malam Yang Dijual Dikota Medan Secara Spektrofotometri Ultraviolet Metode Dual Wavelenght - Fauziah Zain; Nia Novranda Pertiwi; Minda Sari Lubis; Rafita Yuniarti (CV. Creative Tugu Pena, 2024)
Night cream is a mixture of chemicals and/or other ingredients with the property of whitening the skin or lightening black spots on the skin that is used at night. Hydroquinone is a compound that is often used as a bleach in cosmetics. Excessive use can have dangerous effects on the skin because it can cause skin disorders and can even cause skin cancer. Retinoic acid is prohibited from being used in whitening creams because it can cause dry skin, burning sensation, carcinogenic and teratogenic. This research aims to determine the presence of hydroquinone and retinoic acid compounds and to determine the levels of hydroquinone and retinoic acid in night cream preparations sold in the city. Medan. In this study, 4 samples were taken with different trademarks and given the initials A, B, C, D. At the sample testing stage, color reagents were tested qualitatively and quantitative tests were used using UV spectrophotometry with the dual Wavelength method. Based on the results of research conducted on 4 night cream samples, all night cream samples in the city of Medan contained hydroquinone and retinoic acid compounds and the levels obtained in each sample were that the levels in hydroquinone in night cream A, 2.184%, in night cream B were 2.713%. %, in night cream C 2.543%, and in night cream D 4.402%. Retinoic acid was found in night cream A 0.032%, in night cream B 0.033%, in night cream C 0.039, and in night cream D 0.0023%.